The intragraft vascularized bone marrow induces secondary donor-specific mystacial pad allograft tolerance - Lin, Cheng-Hung; Anggelia, Madonna Rica; Cheng, Hui-Yun; Hsieh, Yun-Huan; Chuang, Wen-Yu; Yang, Huang-Yu; Lin, Chih-Hung (Frontiers in Immunology, 2022)
Vascularized bone marrow (VBM) is essential in tolerance induction through chimerism. We hypothesized that the inclusion of VBM contributes to the induction of mystacial-pad allotransplantation tolerance. In this study, nineteen VBM, nine mystacial pad, and six sequential VBM and mystacial pad allografts were transplanted from Brown-Norway (BN) rats to Lewis (Lew) rats to test our hypothesis. The VBM recipients were divided into ALS monotherapy group (two doses of antilymphocyte serum (ALS) on day 3 pre- and day 1 post-transplantation), immunosuppressant group (a week of 2mg/kg/day Tacrolimus (Tac) and 3 weeks of 3mg/kg/day rapamycin (RPM)), and combined therapy group. The mystacial pad recipients were divided into VBM and non-VBM transplantation group, and both groups were treated with immunosuppression regimen that consists ALS, Tac, and RPM. For the recipients of sequential VBM and mystacial pad allotransplantations, additional Tac was given 1 week after mystacial pad transplantation. Allograft survival, donor-specific tolerance, and chimerism level were evaluated. With the administration of ALS and short-term Tac and RPM treatments, VBM recipients demonstrated long-term graft survival (>120 days) with persistent chimerism for 30 days. CD3+ T cells from tolerant rats showed donor-specific hyporesponsiveness and tolerance to donor skin grafts but not to third-party counterparts. Furthermore, mystacial pad graft recipients with VBM transplantation exhibited a higher allograft survival rate than those without VBM transplantation (MST > 90 days vs. 70 days, p < 0.05). This study demonstrated that VBM transplantation is an efficient strategy to induce and maintain donor-specific tolerance for an osseous-free allograft.